On the autonomy of the National Jury of Elections - Mendoza Ramírez, Enrique Javier (2007)
Considering main part of all Constitutional Government, the present work will try to show the importance of the work of the National Jury of Elections as a supreme interpreter in electoral matter; moreover, in the second part, it will raise some concerns referred to the serious threats against the autonomy of the constitutional independent organisms that come to mean the excesses of the last jurisprudences of the Constitutional Court.